Kisah dan Pendidikan Karakter Anak Usia Dini - Rahma, Aulia (ACIECE, 2018)
Story and character education are two very important things in early childhood education. Storyis a method for conveying messages through an event. Whereas character education is an effortor guidance that aims to shape a child's personality. Character value in early childhood is a verybasic value that must be owned by each individual, therefore, steps to develop it through thereality of living together that make children feel the goodness of that value. One method incharacter education is through stories, in which the story is one of the expressions in the Qur'anwhich can be grouped into historical, parable, and amateur stories. The story has benefitsincluding, it can arouse the awareness of the reader or listener, be able to direct emotions, andcontain ibrah which can be used as a lesson. As with other character education methods, storiesalso have advantages and disadvantages